Cellular intrinsic mechanism affecting the outcome of AML treated with Ara-C in a syngeneic mouse model. - Wenjun Zhao (Public Library of Science (PLoS), 2014)
The mechanisms underlying acute myeloid leukemia (AML) treatment failure are not clear. Here, we established a mouse model of AML by syngeneic transplantation of BXH-2 derived myeloid leukemic cells and developed an efficacious Ara-C-based regimen for treatment of these mice. We proved that leukemic cell load was correlated with survival. We also demonstrated that the susceptibility of leukemia cells to Ara-C could significantly affect the survival. To examine the molecular alterations in cells with different sensitivity, genome-wide expression of the leukemic cells was profiled, revealing that overall 366 and 212 genes became upregulated or downregulated, respectively, in the resistant cells. Many of these genes are involved in the regulation of cell cycle, cellular proliferation, and apoptosis. Some of them were further validated by quantitative PCR. Interestingly, the Ara-C resistant cells retained the sensitivity to ABT-737, an inhibitor of anti-apoptosis proteins, and treatment with ABT-737 prolonged the life span of mice engrafted with resistant cells. These results suggest that leukemic load and intrinsic cellular resistance can affect the outcome of AML treated with Ara-C. Incorporation of apoptosis inhibitors, such as ABT-737, into traditional cytotoxic regimens merits consideration for the treatment of AML in a subset of patients with resistance to Ara-C. This work provided direct in vivo evidence that leukemic load and intrinsic cellular resistance can affect the outcome of AML treated with Ara-C, suggesting that incorporation of apoptosis inhibitors into traditional cytotoxic regimens merits consideration for the treatment of AML in a subset of patients with resistance to Ara-C.